Analysis of Wastewater Quality at the Indonesian Red Cross (PMI) in Cilacap Regency - Rakhmawati, Nita Sofia; Widuri, Hasri; Febrianti, Tessa Sukma (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2025)
Introduction: Increasing volume of medical wastewater presents a significant challenge for environmental management, particularly in healthcare facilities such as the Blood Donor Unit (UDD) of the Indonesian Red Cross (PMI). Inadequate wastewater treatment can lead to environmental pollution and pose serious public health risks. This study aimed to evaluate the performance of a Wastewater Treatment Plant (WWTP) at the UDD PMI in the Cilacap Regency by analyzing key physical, chemical, and biological parameters.Methods: This study employed a descriptive, quantitative approach. Wastewater samples were collected from the WWTP outlet using random sampling. The samples were placed in sterile bottles, stored at low temperatures, and analyzed at Cilacap Environmental Agency Laboratory using standardized methods for water and wastewater examination (APHA, 2017). The parameters tested included pH, Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), oil and grease, ammonia, and total coliform.Results: The physical parameter (TSS: 18 mg/L) and chemical parameters (pH: 8.0; BOD: 7 mg/L; COD: 10 mg/L; oil and grease: 1.9 mg/L; ammonia: <0.01 mg/L) were all within acceptable regulatory limits. However, the biological parameter of total coliforms exceeded the permissible threshold (>24,000 MPN/100 mL), indicating possible fecal contamination. This result highlights a significant risk to both public health and the environment.Conclusion: Although WWTP are equipped with standard treatment units, their disinfection process is insufficient, posing the potential risk of waterborne disease transmission (e.g., cholera). Therefore, immediate improvements in disinfection systems are recommended.